1980
DOI: 10.1111/j.1600-0447.1980.tb00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral and bilateral ECT in elderly patients A COMPARATIVE STUDY

Abstract: Twenty-nine depressed elderly patients receiving ECT were randomly assigned to a unilateral or bilateral group; post-ictal recovery times, memory changes, and clinical improvement during and after each course were measured by blind and independent observers. All patients but one showed full recovery on testing 3 weeks after treatment. There was no significant difference between the unilateral and bilateral groups either in terms of improvement or the number of treatments needed in each course. A good outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(38 citation statements)
references
References 35 publications
2
35
1
Order By: Relevance
“…Unilateral and bilateral ECT were both effective in those patients completing six study treatments. This result supports the report that unilateral was as effective as bilateral ECT after five treatments (Fraser and Glass, 1980).…”
Section: Efsectivenesssupporting
confidence: 93%
“…Unilateral and bilateral ECT were both effective in those patients completing six study treatments. This result supports the report that unilateral was as effective as bilateral ECT after five treatments (Fraser and Glass, 1980).…”
Section: Efsectivenesssupporting
confidence: 93%
“…None of the case studies reported lack of efficacy of ECT. Folstein et al, 1975) were reported in two trials (Fraser and Glass, 1980;Kellner et al, 1992). Selfrated global memory function improved both in patients treated with titrated, moderate-dose and fixed, high-dose right unilateral ECT .…”
Section: B Non-randomised Studiesmentioning
confidence: 85%
“…This study concerns a post-hoc analysis of data on elderly that participated in a trial by Gregory et al (1985). Unilateral ECT was more effective than bilateral ECT in the short-term (after five treatments), but not in the longer run (after three weeks of treatment) (Fraser et al, 1980). Significantly more patients improved in a three-times-weekly treatment than in the once weekly ECT condition (Kellner et al, 1992).…”
Section: General Remarks On Methodological Aspectsmentioning
confidence: 97%
“…Many studies have documented the effectiveness of ECT in older adults (249)(250)(251). Some investigators report the response as good in elderly as in young people (252), whereas others suggest that the response is less optimal in the oldest old (253).…”
Section: Biologicalmentioning
confidence: 99%